Genetic Diversity Analysis in Boro Rice (Oryza sativa L.) Landraces of Bangladesh using SSR Markers (Bangladesh Rice Journal, 2025)
Genetic diversity and associations among 96 Boro rice landraces of Bangladesh were assessed using 12 SSR markers at the Genetic Resources and Seed Division of Bangladesh Rice Research Institute (BRRI). The number of alleles per locus ranged from 11 (RM163) to 41 (RM283), with a mean of 21 alleles. Polymorphism information content (PIC) ranged from 0.75 (RM163) to 0.95 (RM283) with an average of 0.891, showing a large variability among the tested landraces. PIC values showed that RM283 was considered as the best marker for identifying and evaluating the diversity of Boro rice landraces. The frequency of most common alleles at each locus ranged from 8% (RM283) to 34% (RM275, RM277). Nei’s genetic distance based UPGMA dendrogram grouped the studied landraces into seven different clusters with a similarity coefficient of 0.11. Based on the dendrogram constructed using SSR markers, the accessions that are distant from each other in terms of genetic distance and diversity index (such as Pashusail and Tulsi Boro; Raja sail and Kali Boro; Bashful and Jamir; Begun bitchi and Boro deshi; Banjira and Bogra (Deshi); Jagli Boro and Lahi Boro; Bimion and Gorchi sail; Jhati sail and Khaia Boro; Tepi Boro and Jamir Boro) are strongly recommended for selection as parents in future breeding programmes aimed at developing high-yielding and stress-resilient rice variety in contribution to global food security. The results of this study could be useful for the identification of genetically diverse parents from the landraces for breeding programme aimed at varietal improvement.Bangladesh Rice J. 27(2): 1-16, 2023